Skin-impedance in Fabry Disease: A prospective, controlled, non-randomized clinical study - Gupta, Surya N; Ries, Markus; Murray, Gary J; Quirk, Jane M; Brady, Roscoe O; Lidicker, Jeffrey R; Schiffmann, Raphael; Moore, David F (BMC neurology, 2008)
Background We previously demonstrated improved sweating after enzyme replacement therapy (ERT) in Fabry disease using the thermo-regularity sweat and quantitative sudomotor axon reflex tests. Skin-impedance, a measure skin-moisture (sweating), has been used in the clinical evaluation of burns and pressure ulcers using the portable dynamic dermal impedance monitor (DDIM) system. Methods We compared skin impedance measurements in hemizygous patients with Fabry disease (22 post 3-years of bi-weekly ERT and 5 ERT naive) and 22 healthy controls. Force compensated skin-moisture values were used for statistical analysis. Outcome measures included 1) moisture reading of the 100 th repetitive reading, 2) rate of change, 3) average of 60–110 th reading and 4) overall average of all readings. Results All outcome measures showed a significant difference in skin-moisture between Fabry patients and control subjects (p < 0.0001). There was no difference between Fabry patients on ERT and patients naïve to ERT. Increased skin-impedance values for the four skin-impedance outcome measures were found in a small number of dermatome test-sites two days post-enzyme infusions. Conclusion The instrument portability, ease of its use, a relatively short time required for the assessment, and the fact that DDIM system was able to detect the difference in skin-moisture renders the instrument a useful clinical tool.